Comparative characteristics of WAVE and RYDE in the terms of security and performance - Telnova, A. A.; Hrinenko, T. O. (ХНУРЕ, 2025)
The purpose of this paper is to study and compare code-based and MPC signatures on the example of WAVE and RYDE digital signatures, which will serve as a basis for further analysis of these digital signature mechanisms.
Keywords: WAVE; RYDE